Determinants of students' entrepreneurial intention : an empirical research - Zovko, Luka (Array, 2020)
As to contribute to the literature on entrepreneurial intention, a survey was conducted on a sample of Croatian students and their entrepreneurial intentions, by using Ajzen's (1991) theory of planned behaviour. This theory determines intention through attitudes, behavioural control (self-efficacy), and social norms. Additional four determinants were investigated: role models, education, needs for achievement, and propensity towards risk. We propose that individuals exposed to role models and entrepreneurial education, as well as those who have a higher level of need for achievement and propensity towards risk, are more likely to set up a venture. The survey was conducted at the Faculty of Economics, Business and Tourism, University of Split, Croatia and the obtained data were analysed by using the structural equation modelling technique. A total of 160 survey responses from students were obtained. It was found that attitudes and propensity towards risk positively affect entrepreneurial intention. Surprisingly, self-efficacy and social norms, in addition to role models, education, and the need for achievement, failed to produce a significant effect on entrepreneurial intention.